Non-cryopreserved peripheral blood progenitor cells collected by a single very large-volume leukapheresis: A simplified and effective procedure for support of high-dose chemotherapy - Papadimitriou, C.A.; Dimopoulos, M.A.; Kouvelis, V.; Kostis, E.; Kapsimali, V.; Contoyannis, D.; Anagnostopoulos, A.; Papadimitris, C.; Kiamouris, C.; Gika, D.; Nanas, J.; Athanassiades, P.; et al. (Journal of Clinical Apheresis, 2000)
High-dose chemotherapy with autologous peripheral blood progenitor cell (PBPC) support has become a widely used treatment strategy. In order to simplify the procedure, a single very large-volume leukapheresis, programme combined with short-term refrigerated storage of the PBPC was developed. Seventy-two patients suffering from various relatively chemosensitive malignancies received high-dose chemotherapy, consisting of agents with short in vivo half-lives and 24 to 48 hours later, the refrigerated PBPC were reinfused. A single very large-volume apheresis was sufficient to obtain at least 2 × 106/kg CD34+ cells in 58 patients, (81%). and 63% had at least 2.5 × 106 CD34+ cells/kg. Only two patients (3%) were transplanted with less than 1 × 10 CD34+ cells/kg. In three patients (4%) leukupheresis was repeated because of insufficient number of PBPC. The median CD34+ cell count was 3 × 106/kg. A median of 38.5 L blood (range, 21 to 59) was processed, which accounted for a median of 9 × patient's total blood volume. Very large-volume leukapharesis was well tolerated with symptomatic hypocalcemia being the most common (18%) side-effect. The median time to neutrophils >1.5 × 109/L, and to self-supporting platelet COUDI >25 × 109/L, was 10 and 12 days after reinfusion of PBPC graft, respectively. There were no treatment-related deaths. Our results indicate that this simplified approach of PBPC transplantation can be associated with prompt hematologic recovery in most patients and that it can be useful in settings where facilities are limited or for certain diseases where conditioning regimens with short hall-life are appropriate. © 2000 Wiley-Liss, Inc.
Keywords: Blood stem cell transplantation; Large-volume apheresis; Refrigerated storage